Resin composition
By combining resin compositions of epoxy resin, active ester compound and specific compounds, the problem of prone to cracking after decontamination is solved, and the effect of low dielectric properties and high adhesion of conductor layer is achieved.
Patent Information
- Application Number
- CN202411121191.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-18
- Filing Date
- 2024-08-15
- Publication Date
- 2025-02-21
AI Technical Summary
The conventional resin composition is prone to cracks after decontamination treatment, and it is difficult to improve the dielectric properties of the insulating layer and the adhesion between the conductor layers.
By combining resin compositions containing epoxy resin, active ester compound and specific compound, cured products with low melt viscosity, low dielectric properties and high adhesion of conductor layers were prepared.
The effect of suppressing cracks after decontamination treatment is achieved, and the dielectric characteristics of the insulating layer and the adhesion between the conductor layers are improved.
Smart Images

Figure CN119490727A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition and further to a resin sheet, a printed wiring board and a semiconductor device obtained by using the resin composition. Background Art
[0002] As a manufacturing technology for a printed wiring board, a manufacturing method using a stacking method in which insulating layers and conductive layers are alternately stacked is known.
[0003] As an insulating material for a printed wiring board used in such an insulating layer, for example, Patent Document 1 discloses a resin composition.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2023 / 008079 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In recent years, with the high functionality of printed wiring boards, it is sought to further improve the dielectric properties such as the dielectric loss tangent of the insulating layer and further improve the adhesion between the plating layers. In addition, with the high functionality of printed wiring boards, in order to bury fine wiring with a resin composition, it is also sought to reduce the melt viscosity of the resin composition.
[0009] Furthermore, when an insulating layer is formed using a conventional resin composition that contributes to good dielectric properties, the resulting insulating layer tends to be easily cracked after desmear treatment.
[0010] The present invention is made in view of the above-mentioned problems, and provides a resin composition with low melt viscosity, which can obtain a cured product with low dielectric properties, high adhesion (peel strength) between conductor layers, and the ability to suppress cracking after desmearing treatment; a resin sheet containing the resin composition; a printed wiring board having an insulating layer formed using the resin composition; and a semiconductor device.
[0011] Means used to solve problems
[0012] The present inventors have conducted intensive studies on the above-mentioned problems and have found that the above-mentioned problems can be solved by combining (A) an epoxy resin, (B) an active ester compound, and (C) a compound represented by the formula (C-1), thereby completing the present invention.
[0013] That is, the present invention includes the following contents.
[0014] [1] A resin composition comprising:
[0015] (A) Epoxy resin;
[0016] (B) an active ester compound; and
[0017] (C) A compound represented by formula (C-1).
[0018] [Chemistry 1]
[0019]
[0020] In the formula, X each independently represents an n-valent hydrocarbon group optionally having a substituent; Y each independently represents a monovalent group optionally having a substituent and containing a double bond; Ar each independently represents a divalent aromatic hydrocarbon group having two alkyl groups optionally being the same or different as substituents; Z each independently represents a single bond or a divalent aromatic hydrocarbon group optionally having a substituent. n represents an integer of 1 to 3; m represents an integer of 1 to 100.
[0021] [2] The resin composition according to [1], wherein Y represents any one of an acryloyl group, a methacryloyl group, and a vinylbenzyl group.
[0022] [3] The resin composition according to [1] or [2], wherein the component (C) contains a compound represented by formula (C-2).
[0023] [Chemistry 2]
[0024]
[0025] In the formula, R 1 and R 2 Each independently represents a monovalent group containing a double bond; R 3 and R 4 Each independently represents a divalent aromatic hydrocarbon group having two alkyl groups which may be the same or different as substituents; R 5 Each independently represents a divalent aromatic hydrocarbon group; R 6 represents a single bond or a divalent aromatic hydrocarbon group which may have a substituent. m1 represents an integer of 1-100.
[0026] [4] The resin composition according to any one of [1] to [3], wherein the component (C) contains a compound represented by formula (C-3).
[0027] [Chemistry 3]
[0028]
[0029] In the formula, R 11 and R 12 Each independently represents a monovalent group containing a double bond; R 13 and R 14Each independently represents a divalent aromatic hydrocarbon group having two alkyl groups which may be the same or different as substituents; R 15 represents a single bond or a divalent aromatic hydrocarbon group which may have a substituent. m2 represents an integer of 1-100.
[0030] [5] The resin composition according to any one of [1] to [4], wherein the content of the component (C) is 1% by mass or more and 25% by mass or less, based on 100% by mass of the resin component in the resin composition.
[0031] [6] The resin composition according to any one of [1] to [5], further comprising (D) an inorganic filler.
[0032] [7] The resin composition according to any one of [1] to [6], further comprising (E) a compound having a double bond.
[0033] [8] The resin composition according to [7], wherein the content of the component (E) is 1% by mass or more and 25% by mass or less, based on 100% by mass of the resin component in the resin composition.
[0034] [9] The resin composition according to any one of [1] to [8], further comprising (F) a curing agent.
[0035]
[10] A resin sheet comprising a support and a resin composition layer, wherein the resin composition layer is provided on the support and comprises the resin composition according to any one of [1] to [9].
[0036]
[11] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to [9].
[0037]
[12] A semiconductor device comprising the printed wiring board described in
[11] .
[0038] Effects of the Invention
[0039] According to the present invention, there can be provided a resin composition having a low melt viscosity, which can obtain a cured product having low dielectric properties, high adhesion between conductor layers, and capable of suppressing the generation of cracks after desmear treatment; a resin sheet comprising the resin composition; a printed wiring board having an insulating layer formed using the resin composition; and a semiconductor device. DETAILED DESCRIPTION
[0040] Hereinafter, the present invention will be described in detail based on its preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be implemented with arbitrary changes within the scope of the claims of the present invention and their equivalents.
[0041] [Resin composition]
[0042] The resin composition of the present invention contains (A) an epoxy resin, (B) an active ester compound and (C) a compound shown in formula (C-1). In the present invention, by combining the components (A), (B) and (C), a resin composition with low melt viscosity can be obtained, and the resin composition can obtain a cured product with low dielectric properties, high adhesion between conductor layers, and the ability to suppress cracking after decontamination treatment. In addition, a cured product with a high glass transition temperature can also be obtained.
[0043] [Chemistry 4]
[0044]
[0045] In the formula, X each independently represents an n-valent hydrocarbon group optionally having a substituent; Y each independently represents a monovalent group optionally having a substituent and containing a double bond; Ar each independently represents a divalent aromatic hydrocarbon group having two alkyl groups optionally being the same or different as substituents; Z each independently represents a single bond or a divalent aromatic hydrocarbon group optionally having a substituent. n represents an integer of 1 to 3; m represents an integer of 1 to 100.
[0046] The resin composition may be combined with components (A) to (C) and further include optional components. Optional components include, for example, (D) inorganic fillers, (E) compounds having double bonds, (F) curing agents, (G) organic fillers, (H) curing accelerators, (I) other additives, and (J) solvents. The following describes each component included in the resin composition in detail.
[0047] <(A) Epoxy resin>
[0048] The resin composition contains (A) epoxy resin as the (A) component. By making the resin composition contain (A) epoxy resin, a cured product showing good mechanical strength and insulation reliability can be obtained. (A) Epoxy resins can be used alone or in combination of two or more.
[0049] Examples of the epoxy resin (A) include biphenylol epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bisphenol AF epoxy resins, dicyclopentadiene epoxy resins, trisphenol epoxy resins, naphthol novolac epoxy resins, phenol novolac epoxy resins, tert-butyl-catechol epoxy resins, naphthalene epoxy resins, naphthol epoxy resins, anthracene epoxy resins, glycidylamine epoxy resins, glycidyl ester epoxy resins. Epoxy resins include epoxy resins of the type having a cyclohexane structure, epoxy resins of the type having a cyclohexanedimethanol structure, epoxy resins of the type having a naphthyl ether structure, epoxy resins of the type having a trimethylol group, epoxy resins of the type having a tetraphenylethane structure, epoxy resins of the type having a phenol benzopyrrolidone structure, epoxy resins of the type having a cyclohexane structure, epoxy resins of the type having a cyclohexane structure, epoxy resins of the type having a cyclohexane structure, epoxy resins of the type having a cyclohexane structure, epoxy resins of the type having a cyclohexane structure, epoxy resins of the type having a naphthyl ether structure, epoxy resins of the type having a trimethylol group, epoxy resins of the type having a tetraphenylethane structure, epoxy resins of the type having a phenol benzopyrrolidone structure, etc. The epoxy resins may be used alone or in combination of two or more.
[0050] The resin composition preferably contains an epoxy resin having two or more epoxy groups in one molecule as component (A). From the viewpoint of significantly obtaining the desired effect of the present invention, the proportion of the epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more relative to 100% by mass of the epoxy resin (A).
[0051] Epoxy resins include epoxy resins that are liquid at a temperature of 20°C (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20°C (hereinafter sometimes referred to as "solid epoxy resins"). In the resin composition, as component (A), only a liquid epoxy resin may be included, only a solid epoxy resin may be included, or a liquid epoxy resin and a solid epoxy resin may be included in combination. Among them, from the viewpoint of significantly obtaining the effects of the present invention, it is preferred to include a liquid epoxy resin and a solid epoxy resin in combination.
[0052] As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred.
[0053] As the liquid epoxy resin, preferred are bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexanedimethanol type epoxy resin, glycidyl amine type epoxy resin and epoxy resin having a butadiene structure, glycidyl cyclohexane type epoxy resin, phenol benzopyrrolidone type epoxy resin, alkyl diglycidyl ether type epoxy resin, and more preferred are bisphenol A type epoxy resin, bisphenol F type epoxy resin, and naphthalene type epoxy resin.
[0054] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "Epico 828EL" (bisphenol A-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" (glycidylamine-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; and "EPI-828" (bisphenol A-type epoxy resins) manufactured by Nippon Steel Chemical & Material. "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nagecemtex Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Daicel Co., Ltd.; "Cellocid 2021P" (alicyclic epoxy resin with ester skeleton) manufactured by Daicel Co., Ltd.; "PB-3600" (epoxy resin with butadiene structure) manufactured by Daicel Co., Ltd.; "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YED216D" (alkyl diglycidyl ether type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd. These can be used alone or in combination of two or more.
[0055] The solid epoxy resin is preferably a solid epoxy resin having two or more epoxy groups in one molecule, more preferably a solid epoxy resin having three or more epoxy groups in one molecule, and more preferably an aromatic solid epoxy resin having three or more epoxy groups in one molecule.
[0056] As the solid epoxy resin, preferred are biphenylol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthyl ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, tetraphenylethane type epoxy resin, and more preferred is biphenyl type epoxy resin.
[0057] Specific examples of the solid epoxy resin include “HP4032H” (naphthalene type epoxy resin), “HP-4700”, “HP-4710” (naphthalene type tetrafunctional epoxy resin), “N-690” (cresol novolac type epoxy resin), “N-695” (cresol novolac type epoxy resin), “HP-7200”, “HP-7200HH”, “HP-7200H” (dicyclopentadiene type epoxy resin), “EXA-7311”, “EXA-7311-G3”, “EXA-7311-G4”, “EXA-7311-G4S”, “HP6000”, “HP6000L” (naphthalene ether type epoxy resin) manufactured by DIC Corporation; “EPPN-502H” (trisphenol type epoxy resin), “NC7000L” (naphthol novolac type epoxy resin), “NC3000H”, “NC3000L” (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. ”, “NC3000L”, “NC3100” (biphenyl type epoxy resin); “ESN475V” (naphthalene type epoxy resin), “ESN485” (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; “YX4000H”, “YL6121” (biphenyl type epoxy resin), “YX4000HK” (biphenyl type epoxy resin), “YX8800” (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation. Resin); "PG-100", "CG-500" manufactured by Osaka Gas Chemical Co., Ltd., "YL7760" (bisphenol AF type epoxy resin), "YL7800" (fluorene type epoxy resin), "jER1010" (solid bisphenol A type epoxy resin), "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "WHR-991S" (phenol benzopyrrolidone type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., etc. These can be used alone or in combination of two or more.
[0058] When a liquid epoxy resin and a solid epoxy resin are used in combination as component (A), the mass ratio of the liquid epoxy resin to the solid epoxy resin is preferably 1:0.1 to 1:20, more preferably 1:0.15 to 1:10, and particularly preferably 1:0.2 to 1:5. By making the mass ratio of the liquid epoxy resin to the solid epoxy resin within this range, the desired effect of the present invention can be significantly obtained.
[0059] The epoxy equivalent of component (A) is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., and further preferably 110 g / eq. to 1000 g / eq. By being in this range, a cured product having a sufficient crosslinking density of the cured product of the resin composition can be achieved. The epoxy equivalent is the mass of an epoxy resin containing 1 equivalent of epoxy groups. The epoxy equivalent can be measured in accordance with JIS K7236.
[0060] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the component (A) is preferably 100 to 5000, more preferably 150 to 3000, and even more preferably 200 to 1500. The weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0061] From the viewpoint of obtaining a cured product showing good mechanical strength and insulation reliability, when the non-volatile component in the resin composition is set to 100% by mass, the content of component (A) is preferably 1% by mass or more, more preferably 3% by mass or more, and further preferably 5% by mass or more. The upper limit is preferably 20% by mass or less, more preferably 15% by mass or less, and particularly preferably 10% by mass or less.
[0062] In the present invention, the content of each component in the resin composition is a value when the nonvolatile component in the resin composition is 100 mass % unless otherwise specified, and the nonvolatile component refers to the entire nonvolatile component in the resin composition excluding the solvent.
[0063] From the viewpoint of obtaining a cured product showing good mechanical strength and insulation reliability, when the resin component in the resin composition is set to 100% by mass, the content of the component (A) is preferably 15% by mass or more, more preferably 20% by mass or more, and further preferably 25% by mass or more, and is preferably 45% by mass or less, more preferably 40% by mass or less, and further preferably 35% by mass or less.
[0064] In addition, in this invention, the resin component in a resin composition means the component other than (D) inorganic filler among the non-volatile components of a resin composition.
[0065] <(B) Active ester curing agent>
[0066] The resin composition contains (B) an active ester curing agent as the (B) component. The (B) active ester curing agent as the (B) component does not contain a substance that conforms to the above-mentioned (A) component. The (B) active ester curing agent usually forms a bond by reacting with the (A) epoxy resin, and can cure the resin composition. By combining the (A) component and the (B) active ester curing agent in the resin composition, a cured product with excellent peel strength can be obtained. The (B) component can be used alone or in combination of two or more.
[0067] As (B) active ester curing agent, it is usually preferred to use esters of phenolic esters, thiophenolic esters, N-hydroxylamine esters, heterocyclic hydroxy compounds, etc., which have ester groups with high reactive activity in 1 molecule. The active ester curing agent is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. Especially from the viewpoint of improving heat resistance, it is preferably an active ester curing agent obtained by carboxylic acid compounds and hydroxy compounds, and more preferably an active ester curing agent obtained by carboxylic acid compounds and phenolic compounds and / or naphthol compounds. As carboxylic acid compounds, for example benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, etc. can be listed. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type biphenol compounds, phenol novolac, etc. Here, the "dicyclopentadiene-type biphenol compound" refers to a biphenol compound obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0068] Specifically, as component (B), dicyclopentadiene type active ester curing agent, naphthalene type active ester curing agent containing naphthalene structure, active ester curing agent containing acetylated product of phenol novolac, active ester curing agent containing benzoylated product of phenol novolac, active ester curing agent as acetylated product of phenol novolac, phosphorus-containing active ester system, active ester curing agent containing styryl and naphthalene structure, etc. can be listed, preferably dicyclopentadiene type active ester curing agent, naphthalene type active ester curing agent containing naphthalene structure. As dicyclopentadiene type active ester curing agent, active ester curing agent containing dicyclopentadiene type biphenol structure is preferred. "Dicyclopentadiene type biphenol structure" means a divalent structural unit containing phenylene-dicyclopentylene-phenylene.
[0069] As commercially available products of component (B), as active ester curing agents containing a dicyclopentadiene-type biphenol structure, there are listed "EXB9451", "EXB9460", "EXB9460S", "EXB-8000L", "EXB-8000L-65M", "EXB-8000L-65TM", "HPC-8000L-65TM", "HPC-8000", "HPC-8000-65T", "HPC-8000H" , "HPC-8000H-65TM" (manufactured by DIC Corporation); as naphthalene-type active ester curing agents containing a naphthalene structure, "HP-B-8151-62T", "EXB-8100L-65T", "EXB-8150-60T", "EXB-8150-62T", "EXB-9416-70BK", "HPC-8150-60T", "HPC-8150-62T", "EXB-8" (manufactured by DIC Corporation) ; As the phosphorus-containing active ester curing agent, "EXB9401" (manufactured by DIC Corporation) can be cited; as the active ester curing agent containing the acetylated product of phenol novolac, "DC808" (manufactured by Mitsubishi Chemical Corporation) can be cited; as the active ester curing agent containing the benzoylated product of phenol novolac, "YLH1026" (manufactured by Mitsubishi Chemical Corporation) can be cited; as the active ester curing agent containing the acetylated product of phenol novolac, "DC808" (manufactured by Mitsubishi Chemical Corporation) can be cited. Company); as active ester curing agents which are benzoyl compounds of phenol novolac, there can be listed “YLH1026” (manufactured by Mitsubishi Chemical Corporation), “YLH1030” (manufactured by Mitsubishi Chemical Corporation), “YLH1048” (manufactured by Mitsubishi Chemical Corporation), and “EXB-8500-65T” (manufactured by DIC Corporation); as active ester curing agents containing styrene and naphthalene structures, there can be listed “PC1300-02-65MA” (manufactured by Aea World Corporation), and the like.
[0070] From the viewpoint of obtaining a cured product having a low dielectric loss tangent and excellent peel strength, the active ester group equivalent of component (B) is preferably 50 g / eq. to 500 g / eq., more preferably 50 g / eq. to 400 g / eq., and even more preferably 100 g / eq. to 300 g / eq. The active ester group equivalent is the mass of the active ester-based curing agent containing 1 equivalent of active ester groups.
[0071] The amount ratio of (A) epoxy resin to (B) active ester curing agent is preferably 0.01 or more, more preferably 0.3 or more, and further preferably 0.5 or more, and preferably 5 or less, more preferably 4 or less, and further preferably 3 or less, in terms of the ratio of [the total number of active groups of active ester curing agent] / [the total number of epoxy groups of epoxy resin]. Here, the "number of epoxy groups of epoxy resin" refers to the value obtained by adding up all the values obtained by dividing the mass of the non-volatile components of epoxy resin present in the resin composition by the epoxy equivalent. In addition, the "number of active groups of active ester curing agent" refers to the value obtained by adding up all the values obtained by dividing the mass of the non-volatile components of active ester curing agent present in the resin composition by the active ester group equivalent. By setting the amount ratio of epoxy resin to active ester curing agent within this range, the effect of the present invention can be significantly obtained.
[0072] From the viewpoint of obtaining a cured product having excellent peel strength, when the nonvolatile component in the resin combination is set to 100% by mass, the content of component (B) is preferably more than 1% by mass, more preferably more than 3% by mass, and further preferably more than 5% by mass. In addition, the upper limit is preferably below 25% by mass, more preferably below 20% by mass, and further preferably below 15% by mass.
[0073] From the viewpoint of obtaining a cured product having excellent peel strength, when the resin component in the resin composition is set to 100% by mass, the content of the component (B) is preferably 20% by mass or more, more preferably 30% by mass or more, and further preferably 35% by mass or more, and is preferably 55% by mass or less, more preferably 50% by mass or less, and further preferably 45% by mass or less.
[0074] <(C) Compound represented by formula (C-1)>
[0075] The resin composition contains a compound represented by formula (C-1) as component (C). The compound represented by formula (C-1) as the component (C) does not include substances that meet the above-mentioned components (A) to (B). By making the resin composition contain component (C), a cured product with low dielectric properties, high adhesion between conductor layers, and the ability to suppress cracking after decontamination treatment can be obtained. Component (C) can be used alone or in combination of two or more in any ratio.
[0076] [Chemistry 5]
[0077]
[0078] In the formula, X each independently represents an n-valent hydrocarbon group optionally having a substituent; Y each independently represents a monovalent group optionally having a substituent and containing a double bond; Ar each independently represents a divalent aromatic hydrocarbon group having two alkyl groups optionally being the same or different as substituents; Z each independently represents a single bond or a divalent aromatic hydrocarbon group optionally having a substituent. n represents an integer of 1 to 3; m represents an integer of 1 to 100.
[0079] n represents an integer of 1 to 3, preferably 2 or 3, and more preferably 2.
[0080] X each independently represents an n-valent hydrocarbon group optionally having a substituent, and the n-valent hydrocarbon group refers to a group obtained by removing n hydrogen atoms from a hydrocarbon compound. Specifically, it represents a monovalent hydrocarbon group, a divalent hydrocarbon group or a trivalent hydrocarbon group. In detail, a monovalent hydrocarbon group refers to a group obtained by removing one hydrogen atom from a hydrocarbon compound, a divalent hydrocarbon group refers to a group obtained by removing two hydrogen atoms from a hydrocarbon compound, and a trivalent hydrocarbon group refers to a group obtained by removing three hydrogen atoms from a hydrocarbon compound. As a hydrocarbon group, for example, a group containing only carbon atoms and hydrogen atoms among the aliphatic groups and aromatic groups described later can be cited. In this specification, an aliphatic group containing only carbon atoms and hydrogen atoms is sometimes referred to as an "aliphatic hydrocarbon group", and an aromatic group containing only carbon atoms and hydrogen atoms is sometimes referred to as an "aromatic hydrocarbon group".
[0081] The number of carbon atoms in the n-valent hydrocarbon group is preferably 2 or more, more preferably 5 or more, and further preferably 10 or more, and is preferably 50 or less, more preferably 40 or less, and further preferably 30 or less or 20 or less. This number of carbon atoms does not include the number of carbon atoms in the substituent.
[0082] The aliphatic hydrocarbon group may be any of a straight chain, a branched chain or a cyclic group. Examples of the aliphatic hydrocarbon group include monovalent aliphatic hydrocarbon groups such as an alkyl group optionally having a substituent and an alkenyl group optionally having a substituent; and divalent aliphatic hydrocarbon groups such as an alkylene group optionally having a substituent and an alkenylene group optionally having a substituent. The number of carbon atoms in the aliphatic hydrocarbon group is the same as that of the n-valent hydrocarbon group, and the number of carbon atoms does not include the number of carbon atoms in the substituent.
[0083] Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a sec-butyl group, an isobutyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, and a cyclohexyl group.
[0084] Examples of the alkenyl group include vinyl, allyl, 1-propenyl, butenyl, sec-butenyl, isobutenyl, tert-butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl and decenyl.
[0085] Examples of the alkylene group include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, and a hexylene group.
[0086] Examples of the alkenylene group include vinylidene, propenylene, butenylene, pentenylene, hexenylene, and the like.
[0087] Examples of the aromatic hydrocarbon group include monovalent aromatic hydrocarbon groups such as aryl groups optionally having substituents; divalent aromatic hydrocarbon groups such as arylene groups optionally having substituents, and the like. The number of carbon atoms of the aromatic hydrocarbon group is preferably 5 or more, more preferably 10 or more, and preferably 50 or less, more preferably 40 or less, and further preferably 30 or less or 20 or less. The number of carbon atoms does not include the carbon atoms of the substituents.
[0088] Examples of the aryl group include phenyl, naphthyl, anthryl, and the like.
[0089] Examples of the arylene group include, for example, phenylene, naphthylene, indanediyldiyl, a group containing indanediyldiyl-phenylene, a group represented by formula (c1), a group represented by formula (c2), and the like. Preferred are indanediyldiyl, a group containing indanediyldiyl-phenylene, a group represented by formula (c1), and a group represented by formula (c2). More preferred are a group containing indanediyldiyl-phenylene, a group represented by formula (c1), and a group represented by formula (c2). Further preferred is a group represented by formula (c2). In the formula, “*” represents a linking bond.
[0090] [Chemical formula 6]
[0091]
[0092] The n-valent hydrocarbon group optionally has a substituent. Examples of the substituent include, for example, a halogen atom, -OH, -O-C 1-6 alkyl, -N(C 1-10 alkyl) 2 , C 1-20 alkyl, C 2-30 alkenyl, C 2-30 alkynyl, C 6-10 aryl, -NH 2 , -CN, -C(O)O-C 1-10 alkyl, -COOH, -C(O)H, -NO 2 , and the like. Among them, as the substituent, C 1-20 alkyl is preferred, C 1-10 alkyl is more preferred, C 1-3 alkyl is further preferred, and methyl is particularly preferred. Here, the term “C p-q ” (p and q are positive integers satisfying p < q.) means that the number of carbon atoms of the organic group described immediately after this term is p to q. For example, the expression “C 1-10 alkyl” means an alkyl group having 1 to 10 carbon atoms. These substituents may optionally bond to each other to form a ring, and the ring structure also includes a spiro ring and a fused ring.
[0093] As X in formula (C-1), it is preferably a divalent aromatic hydrocarbon group optionally having a substituent, more preferably an arylene group, further preferably an indanediyl group, a group containing an indanediyl-phenylene group, a group represented by formula (c1) or a group represented by formula (c2), further preferably an indanediyl group, a group represented by formula (c1) or a group represented by formula (c2), and particularly preferably a group represented by formula (c2).
[0094] Y each independently represents a monovalent group optionally having a substituent and containing a double bond. The monovalent group containing a double bond can use a group having a carbon-carbon double bond, a carbon-oxygen double bond, and two or more of these double bonds. The carbon-carbon double bond and the carbon-oxygen double bond can have a plurality of them.
[0095] As the monovalent group containing a double bond, for example, vinyl, allyl, vinylbenzyl, styryl, acryloyl, methacryloyl, fumaryl, maleoyl, carbonyl, etc. can be listed. Vinylbenzyl is preferably any one of o-vinylbenzyl, m-vinylbenzyl and p-vinylbenzyl, preferably p-vinylbenzyl. The monovalent group containing a double bond may optionally have a substituent. As a substituent, it is the same as the substituent optionally possessed by the n-valent hydrocarbon group represented by X.
[0096] Among them, Y preferably represents any one of an acryloyl group, a methacryloyl group, and a vinylbenzyl group, and more preferably represents a methacryloyl group.
[0097] Ar each independently represents a divalent aromatic hydrocarbon group having two alkyl groups which may be the same or different as substituents. The divalent aromatic hydrocarbon group preferably has 6 to 20 carbon atoms, more preferably 6 to 15 carbon atoms, and further preferably 6 to 10 carbon atoms. The carbon number does not include the carbon number of the alkyl group as a substituent.
[0098] Examples of the divalent aromatic hydrocarbon group include arylene groups, etc. Examples of the arylene group include phenylene groups, naphthylene groups, indandiyl groups, and groups including indandiyl-phenylene groups, and phenylene groups are preferred.
[0099] The two alkyl groups which may be the same or different as substituents are preferably alkyl groups having 1 to 12 carbon atoms, more preferably alkyl groups having 1 to 10 carbon atoms, further preferably alkyl groups having 1 to 6 carbon atoms, further preferably alkyl groups having 1 to 3 carbon atoms, and particularly preferably methyl groups. The substituents may be the same or different, but are preferably the same from the viewpoint of significantly obtaining the effects of the present invention.
[0100] The bonding positions of the two alkyl groups possessed by Ar as substituents may be any of the ortho, meta and para positions based on the site bonded to the oxygen atom in formula (C-1). From the viewpoint of significantly obtaining the effects of the present invention, the two alkyl groups are preferably bonded at the ortho position.
[0101] Z each independently represents a single bond or a divalent aromatic hydrocarbon group which may have a substituent. The divalent aromatic hydrocarbon group preferably has 6 to 20 carbon atoms, more preferably 6 to 15 carbon atoms, and even more preferably 6 to 10 carbon atoms. The carbon number does not include the carbon number of the substituent.
[0102] Examples of the divalent aromatic hydrocarbon group include arylene groups. Examples of the arylene group include phenylene groups and naphthylene groups, and phenylene groups are preferred. The divalent aromatic hydrocarbon group may have a substituent. The substituent is the same as the substituent that the n-valent hydrocarbon group represented by X may have.
[0103] When n represents 2 or 3 as Z, at least one of the plurality of Zs preferably represents a divalent aromatic hydrocarbon group which may have a substituent.
[0104] m represents an integer of 1 to 100, preferably an integer of 1 to 50, more preferably an integer of 1 to 30, and even more preferably an integer of 1 to 20.
[0105] The compound represented by formula (C-1) is preferably a compound represented by formula (C-2).
[0106] [Chemistry 7]
[0107]
[0108] In the formula, R 1 and R 2 Each independently represents a monovalent group containing a double bond; R 3 and R 4 Each independently represents a divalent aromatic hydrocarbon group having two alkyl groups which may be the same or different as substituents; R 5 Each independently represents a divalent aromatic hydrocarbon group; R 6 represents a single bond or a divalent aromatic hydrocarbon group which may have a substituent. m1 represents an integer of 1-100.
[0109] R 1 and R 2 Each independently represents a monovalent group containing a double bond, and is the same as Y in formula (C-1).
[0110] R 3 and R 4 Each independently represents a divalent aromatic hydrocarbon group having two alkyl groups which may be the same or different as substituents, and is the same as Ar in formula (C-1).
[0111] R 5 Each independently represents a divalent aromatic hydrocarbon group. The divalent aromatic hydrocarbon group may optionally have a substituent. As a substituent, it is the same as the substituent optionally possessed by X in formula (C-1). The number of carbon atoms in the divalent aromatic hydrocarbon group is preferably 5 or more, more preferably 10 or more, and preferably 50 or less, more preferably 40 or less, and further preferably 30 or less or 20 or less. The number of carbon atoms does not include the number of carbon atoms of the substituent.
[0112] Examples of the divalent aromatic hydrocarbon group include arylene groups. Examples of the arylene group include phenylene groups, naphthylene groups, indandiyl groups, groups containing indandiyl-phenylene groups, groups represented by formula (c1), and groups represented by formula (c2). Indandiyl groups, groups containing indandiyl-phenylene groups, groups represented by formula (c1), and groups represented by formula (c2) are preferred. Indandiyl groups and groups represented by formula (c2) are more preferred. Groups represented by formula (c2) are further preferred.
[0113] R 6 represents a single bond or a divalent aromatic hydrocarbon group which may have a substituent, and is the same as Z in the formula (C-1).
[0114] m1 represents an integer of 1 to 100, which is the same as m in formula (C-1).
[0115] The compound represented by formula (C-1) is preferably a compound represented by formula (C-3).
[0116] [Chemistry 8]
[0117]
[0118] In the formula, R 11 and R 12 Each independently represents a monovalent group containing a double bond; R 13 and R 14 Each independently represents a divalent aromatic hydrocarbon group having two alkyl groups which may be the same or different as substituents; R 15 represents a single bond or a divalent aromatic hydrocarbon group which may have a substituent. m2 represents an integer of 1-100.
[0119] R 11 and R 12 Each independently represents a monovalent group containing a double bond, and is the same as Y in formula (C-1).
[0120] R 13 and R 14 Each independently represents a divalent aromatic hydrocarbon group having two alkyl groups which may be the same or different as substituents, and is the same as Ar in formula (C-1).
[0121] R 15 represents a single bond or a divalent aromatic hydrocarbon group which may have a substituent, and is the same as the divalent aromatic hydrocarbon group represented by Z in formula (C-1).
[0122] m2 represents an integer of 1 to 100, which is the same as m in formula (C-1).
[0123] Specific examples of the component (C) include the following compounds (Ca) to (Cb). However, the component (C) is not limited to these specific examples. In the formula, m each independently represents an integer of 1 to 100.
[0124] [Chemistry 9]
[0125]
[0126] The component (C) can be synthesized by a known method. The component (C) can be synthesized by the method described in International Publication No. 2023 / 008079, for example.
[0127] From the viewpoint of significantly obtaining the effects of the present invention, the weight average molecular weight of the component (C) is preferably 500 or more, more preferably 1000 or more, and even more preferably 1500 or more, and is preferably 50000 or less, more preferably 10000 or less, and even more preferably 5000 or less.
[0128] From the viewpoint of significantly obtaining the effect of the present invention, when the non-volatile component in the resin composition is set to 100% by mass, the content of the component (C) is preferably 1% by mass or more, more preferably 2% by mass or more, and further preferably 2.5% by mass or more. The upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, and particularly preferably 5% by mass or less.
[0129] From the viewpoint of obtaining a cured product showing good mechanical strength and insulation reliability, when the resin component in the resin composition is set to 100% by mass, the content of the component (C) is preferably 1% by mass or more, more preferably 5% by mass or more, and further preferably 10% by mass or more, and is preferably 25% by mass or less, more preferably 20% by mass or less, and further preferably 15% by mass or less.
[0130] When the content of the component (C) is c1 when the resin component in the resin composition is 100% by mass, and when the content of the component (B) is b1 when the resin component in the resin composition is 100% by mass, b1 / c1 is preferably 0.5 or more, more preferably 1 or more, and further preferably 1.5 or more, and is preferably 10 or less, more preferably 8 or less, and further preferably 5 or less. By adjusting the contents of the components (B) and (C) so that b1 / c1 is within this range, the effect of the present invention can be significantly obtained.
[0131] <(D) Inorganic filler>
[0132] The resin composition may further contain (D) an inorganic filler as an optional component. By making the resin composition contain (D) an inorganic filler, a cured product with low dielectric properties can be obtained. The (D) inorganic filler is usually contained in the resin composition in a particle state. The (D) component can be used alone or in combination of two or more.
[0133] As the material of (D) inorganic filler, inorganic compounds are used. As the material of (D) inorganic filler, for example, silicon dioxide, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate and zirconium tungstate phosphate, etc. can be listed. Among these, silicon dioxide is particularly suitable. As silicon dioxide, for example, amorphous silicon dioxide, fused silica, crystalline silicon dioxide, synthetic silicon dioxide, hollow silica, etc. can be listed. In addition, as silicon dioxide, spherical silicon dioxide is preferably used.
[0134] Examples of commercially available inorganic fillers (D) include "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C500SQ" manufactured by Advantex Corporation; -C2", "SO-C1"; "UFP-30", "DAW-03", "FB-105FD" made by Tokuko Co., Ltd.; "シルフィルNS" made by Tokuman Co., Ltd. S-3N", "Structure NSS-4N", "Structure NSS-5N"; "Structure" and "MGH-005" made by Pacific Cement Company, etc.
[0135] The average particle size of the inorganic filler (D) is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 0.3 μm or more, and is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less.
[0136] (D) The average particle size of the inorganic filler can be measured by the laser diffraction / scattering method based on Mie scattering theory. Specifically, the particle size distribution of the inorganic filler can be prepared according to the volume basis by using a laser diffraction scattering particle size distribution measuring device, and its median particle size is measured as the average particle size. The sample can be measured using a sample obtained by weighing 100 mg of inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it for 10 minutes using ultrasound. For the sample, a laser diffraction particle size distribution measuring device can be used, and the wavelength of the light source used is set to blue and red, and the particle size distribution of the volume basis of the inorganic filler is measured using a flow cell method, and the average particle size is calculated in the form of a median particle size according to the obtained particle size distribution. As a laser diffraction particle size distribution measuring device, for example, "LA-960" manufactured by Horiba Manufacturing Co., Ltd. can be listed.
[0137] (D) The BET specific surface area of the inorganic filler is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, and preferably 100m 2 / g or less, more preferably 70m 2 / g or less, more preferably 40m 2 / g or less.
[0138] (D) The specific surface area of the inorganic filler can be measured by using a specific surface area measuring apparatus (Macsorb HM-1210 manufactured by MacTech Corporation) according to the BET method, adsorbing nitrogen gas on the sample surface, and calculating the specific surface area using the BET multipoint method.
[0139] From the viewpoint of improving moisture resistance and dispersibility, (D) inorganic filler is preferably treated with a surface treatment agent. As the surface treatment agent, for example, fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. can be listed. The surface treatment agent can be used alone or in any combination of two or more.
[0140] Commercially available products of the surface treatment agent include, for example, "KBM403" (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM803" (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBE903" (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "SZ-31" (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM103" (phenyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., "KBM-4803" (long-chain epoxy-type silane coupling agent) manufactured by Shin-Etsu Chemical Co., Ltd., and "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.
[0141] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment by the surface treatment agent is preferably within a specific range. Specifically, 100% by mass of the inorganic filler is preferably surface treated by 0.2% to 5% by mass of the surface treatment agent, more preferably by 0.2% to 3% by mass of the surface treatment agent, and further preferably by 0.3% to 2% by mass of the surface treatment agent.
[0142] The degree of surface treatment by the surface treatment agent can be evaluated based on the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler is preferably 0.02 mg / m 2 More preferably 0.1 mg / m 2 More preferably, 0.2 mg / m 2 On the other hand, from the viewpoint of preventing the melt viscosity of the resin composition from increasing, it is preferably 1.0 mg / m 2 Below, more preferably 0.8 mg / m 2 Below, more preferably 0.5 mg / m 2 the following.
[0143] (D) The amount of carbon per unit surface area of the inorganic filler can be measured by washing the surface-treated inorganic filler with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler surface-treated with a surface treatment agent, and ultrasonically cleaned at 25°C for 5 minutes. After the supernatant can be removed and the solid component is dried, a carbon analyzer can be used to measure the amount of carbon per unit surface area of the inorganic filler. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd., etc. can be used.
[0144] In addition, the degree of surface treatment using a surface treatment agent can be evaluated according to the amount of carbon per unit mass of the inorganic filler. The amount of carbon per unit mass of the inorganic filler is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, further preferably 0.1% by mass or more, in addition, preferably 1.0% by mass or less, more preferably 0.8% by mass or less, further preferably 0.5% by mass or less. (D) The amount of carbon per unit mass of the inorganic filler can be measured using a carbon analyzer in the same manner as the amount of carbon per unit surface area of the inorganic filler (D).
[0145] When the non-volatile component in the resin composition is set to 100 mass%, the content of the (D) inorganic filler is preferably 60 mass% or more, more preferably 65 mass% or more, particularly preferably 70 mass% or more, and is preferably 90 mass% or less, more preferably 85 mass% or less, particularly preferably 80 mass% or less.
[0146] <(E) Compounds Having Double Bonds>
[0147] The resin composition may contain (E) a compound having a double bond as an optional component. The compound having a double bond as the component (E) does not include substances that meet the above-mentioned components (A) to (D). The component (E) may be used alone or in combination of two or more in any ratio.
[0148] (E) component can use a compound having a carbon-carbon double bond, and (E) component can have multiple carbon-carbon double bonds. Carbon-carbon double bonds are preferably present in the form of free radical polymerizable unsaturated groups. Thus, (E) component is preferably a free radical polymerizable compound having free radical polymerizable unsaturated groups. As the free radical polymerizable unsaturated group, for example, a group containing an olefinic double bond can be listed.
[0149] Examples of the free radical polymerizable unsaturated group include vinyl, allyl, vinylphenyl, acryloyl, methacryloyl, fumaryl, and maleoyl. The number of the free radical polymerizable unsaturated groups contained in the (E) component is usually 1 or more, preferably 2 or more. When the (E) component contains 2 or more free radical polymerizable unsaturated groups, these 2 or more free radical polymerizable unsaturated groups may be the same or different.
[0150] Examples of the component (E) include allyl radical polymerizable compounds, (meth)acrylic radical polymerizable compounds, styrene radical polymerizable compounds, and maleimide radical polymerizable compounds. Among them, styrene radical polymerizable compounds and maleimide radical polymerizable compounds are preferred.
[0151] Allyl radical polymerizable compounds are compounds having, for example, one or more, preferably two or more allyl groups. Examples of allyl radical polymerizable compounds include aromatic carboxylic acid allyl ester compounds such as diallyl biphenylate, triallyl trimellitate, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, 2,6-naphthalenedicarboxylate, and 2,3-naphthalenedicarboxylate; isocyanurate allyl ester compounds such as 1,3,5-triallyl isocyanurate and 1,3-diallyl-5-glycidyl isocyanurate; and 2,2 - Aromatic allyl compounds containing epoxy groups such as bis[3-allyl-4-(glycidyloxy)phenyl]propane; aromatic allyl compounds containing benzoxazine such as bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane; aromatic allyl compounds containing ethers such as 1,3,5-triallyl ether benzene; allyl silane compounds such as diallyldiphenylsilane; resins containing multiple benzene rings and allyl groups, etc. Examples of commercially available allyl radical polymerizable compounds include “TAIC” (1,3,5-triallyl isocyanurate) manufactured by Nippon Chemical Industry Co., Ltd., “DAD” (diallyl biphenylate) manufactured by Nichido Technofurano Chemical Co., Ltd., “TRIAM-705” (triallyl trimellitate) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., “DAND” (diallyl 2,3-naphthalenecarboxylate) manufactured by Nichido Technofurano Chemical Co., Ltd., and “ALP-d” manufactured by Shikoku Chemical Industry Co., Ltd. "(Bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane), "RE-810NM" (2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane) manufactured by Nippon Kayaku Co., Ltd.), "DA-MGIC" (1,3-diallyl-5-glycidyl isocyanurate) manufactured by Shikoku Chemical Industry Co., Ltd.), "NE-V-1100-70T" (resins containing multiple benzene rings and allyl groups) manufactured by DIC Corporation, etc.
[0152] The (meth)acrylic radical polymerizable compound is, for example, a compound having one or more, preferably two or more, acryloyl groups and / or methacryloyl groups. Examples of the (meth)acrylic radical polymerizable compound include low molecular weight (molecular weight less than 1000) aliphatic (meth)acrylate compounds such as cyclohexane-1,4-dimethanol di(meth)acrylate, cyclohexane-1,3-dimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, glycerol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and low molecular weight (molecular weight less than 1000) ether-containing (meth)acrylate compounds such as alcohol di(meth)acrylate, 3,6,9-trioxaundecane-1,11-diol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate; low molecular weight (molecular weight less than 1000) isocyanurate-containing (meth)acrylate compounds such as tris(3-hydroxypropyl)isocyanurate tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, ethoxylated isocyanuric acid tri(meth)acrylate; high molecular weight (molecular weight of 1000 or more) acrylate compounds such as (meth)acrylic modified polyphenylene ether resin, etc. Commercially available products of the (meth)acrylic radical polymerizable compound include, for example, "A-DOG" (dioxanediol diacrylate) manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "DCP-A" (tricyclodecane dimethanol diacrylate) and "DCP" (tricyclodecane dimethanol dimethacrylate) manufactured by Kyoeisha Chemical Co., Ltd., "KAYARAD R-684" (tricyclodecane dimethanol diacrylate) and "KAYARAD R-604" (dioxanediol diacrylate) manufactured by Nippon Kayaku Co., Ltd., and "SA9000" and "SA9000-111" (methacrylic modified polyphenylene ether) manufactured by SABIC.
[0153] Styrene-based free radical polymerizable compounds are, for example, compounds having one or more, preferably two or more, vinyl groups directly bonded to aromatic carbon atoms. Examples of styrene-based free radical polymerizable compounds include low molecular weight (molecular weight less than 1000) styrene-based compounds such as divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, and bis(4-vinylphenyl)ether; and high molecular weight (molecular weight greater than 1000) styrene-based compounds such as vinylbenzyl-modified polyphenylene ether resins and styrene-divinylbenzene copolymers. Examples of commercially available styrene-based radical polymerizable compounds include “ODV-XET (X03)”, “ODV-XET (X04)”, and “ODV-XET (X05)” (styrene-divinylbenzene copolymers) manufactured by Nippon Steel Chemical & Material Co., Ltd., and “OPE-2St 1200” and “OPE-2St 2200” (vinyl benzyl-modified polyphenylene ether resins) manufactured by Mitsubishi Gas Chemical Co., Ltd.
[0154] The maleimide-based free radical polymerizable compound is, for example, a compound having one or more, preferably two or more, maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl). The maleimide-based free radical polymerizable compound may be an aliphatic maleimide compound containing an aliphatic amine skeleton, or may be an aromatic maleimide compound containing an aromatic amine skeleton. Commercially available products of maleimide-based radical polymerizable compounds include, for example, "BMI-3000J", "BMI-5000", "BMI-1400", "BMI-1500", "BMI-1700", "BMI-689" (all manufactured by Designer Molecules Inc.), "SLK6895-T90", "SLK-6895", "SLK-1500" (all manufactured by Shin-Etsu Chemical Co., Ltd.), "MIR-3000-70MT" (manufactured by Nippon Kayaku Co., Ltd.), "BMI-4000" (manufactured by Yamato Chemical Co., Ltd.), and "BMI-80" (manufactured by Kaiei Chemical Co., Ltd.). In addition, as the maleimide-based radical polymerizable compound, the maleimide resin (maleimide compound containing an indane ring skeleton) disclosed in the Invention Association's Public Technical Bulletin No. 2020-500211 can be used.
[0155] The ethylenically unsaturated bond equivalent of the component (E) is preferably 20 to 3,000 g / eq., more preferably 50 to 2,500 g / eq., further preferably 70 to 2,000 g / eq., and particularly preferably 90 to 1,500 g / eq. The ethylenically unsaturated bond equivalent refers to the mass of the radical polymerizable compound per 1 equivalent of ethylenically unsaturated bonds.
[0156] The weight average molecular weight of the component (E) is preferably 40,000 or less, more preferably 10,000 or less, further preferably 5,000 or less, and particularly preferably 3,000 or less. The lower limit is not particularly limited, and may be, for example, 150 or more. The weight average molecular weight can be measured as a polystyrene conversion value by gel permeation chromatography (GPC).
[0157] From the viewpoint of significantly obtaining the desired effect of the present invention, when the non-volatile component in the resin composition is set to 100% by mass, the content of the component (E) is preferably 0.5% by mass or more, more preferably 1% by mass or more, and further preferably 1.5% by mass or more, and the upper limit is preferably 8% by mass or less, more preferably 5% by mass or less, and further preferably 3% by mass or less.
[0158] From the viewpoint of significantly obtaining the desired effects of the present invention, for example, from the viewpoint of obtaining a cured product having a high glass transition temperature, the content of the component (E) is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, and is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less or 10% by mass or less, based on 100% by mass of the resin component in the resin composition.
[0159] <(F) Curing agent>
[0160] The resin composition may further contain a (F) curing agent as an optional component. The (F) curing agent as the (F) component does not include substances that meet the above-mentioned (A) to (E) components. As the (F) curing agent, a compound that can react with the (A) component to cure the resin composition can be used, and examples thereof include phenol-based curing agents, naphthol-based curing agents, carbodiimide-based curing agents, benzoxazine-based curing agents, and cyanate-based curing agents. Among them, from the viewpoint of significantly obtaining the effects of the present invention, the (F) curing agent preferably includes a phenol-based curing agent. The (F) curing agent can be used alone or in combination of two or more.
[0161] As the phenolic curing agent and the naphthol curing agent, from the viewpoint of heat resistance and water resistance, a phenolic curing agent having a novolac structure or a naphthol curing agent having a novolac structure is preferred. In addition, from the viewpoint of adhesion with the conductor layer, a nitrogen-containing phenolic curing agent is preferred, and a phenolic curing agent containing a triazine skeleton is more preferred.
[0162] Specific examples of phenol-based curing agents and naphthol-based curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemicals, "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495", "SN-495V", "SN375", and "SN395" manufactured by Nippon Steel & Sumitomo Chemicals Corporation, and "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA3018-50P", "EXB-9500", and "KA-1163" manufactured by DIC Corporation.
[0163] The carbodiimide-based curing agent is a compound having one or more carbodiimide groups (—N═C═N—) in one molecule, and the carbodiimide-based curing agent is preferably a compound having two or more carbodiimide groups in one molecule.
[0164] Specific examples of carbodiimide-based curing agents include commercially available carbodiimide-based curing agents such as Carbodiimide V-03 (carbodiimide group equivalent: 216 g / eq., V-05 (carbodiimide group equivalent: 262 g / eq.), and V-07 (carbodiimide group equivalent: 200 g / eq.) manufactured by Nisshinbo Chemical Co., Ltd.; V-09 (carbodiimide group equivalent: 200 g / eq.); and Stabaksol P (carbodiimide group equivalent: 302 g / eq.) manufactured by Lanxess Co., Ltd.
[0165] Specific examples of the benzoxazine-based curing agent include "HFB2006M" manufactured by Showa Highpolymer Co., Ltd. and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0166] Examples of the cyanate curing agent include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylenediphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylidene))benzene, bis(4-cyanatephenyl)sulfide, and bis(4-cyanatephenyl)ether; and polyfunctional cyanate resins derived from phenol novolac and cresol novolac, and prepolymers obtained by partially triazinizing these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" (phenol novolac type multifunctional cyanate resins), "ULL-950S" (multifunctional cyanate resin), "BA230", "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate is triazine-treated to form a trimer), etc. manufactured by Arxada.
[0167] The amount ratio of component (A) to component (F) is preferably in the range of 1:0.01 to 1:10, more preferably 1:0.05 to 1:8, and further preferably 1:0.08 to 1:5, in terms of the ratio of [the total number of epoxy groups of component (A)]:[the total number of active groups of component (F)]. Here, the "total number of epoxy groups of the epoxy resin" refers to the value obtained by adding up all the values obtained by dividing the mass of the non-volatile components of component (A) present in the resin composition by the epoxy equivalent. In addition, the "total number of active groups of component (F)" refers to the value obtained by adding up all the values obtained by dividing the mass of the non-volatile components of component (F) present in the resin composition by the active group equivalent. As component (F), by setting its amount ratio to component (A) within this range, the effect of the present invention can be significantly obtained.
[0168] The ratio of the amount of component (A) to the amount of component (B) and component (F) is preferably in the range of 1:0.01 to 1:10, more preferably 1:0.3 to 1:5, and even more preferably 1:0.4 to 1:4, in terms of the ratio of [the total number of epoxy groups of component (A)]:[the total number of active groups of component (B) and component (F)]. Here, the "total number of active groups of component (B) and component (F)" refers to the value obtained by adding up all the values obtained by dividing the mass of the non-volatile components of component (B) and component (F) present in the resin composition by the active group equivalent. By setting the ratio of the amount of component (A) to the amount of component (B) and component (F) within this range, the effect of the present invention can be significantly obtained.
[0169] From the viewpoint of significantly obtaining the desired effect of the present invention, when the non-volatile component in the resin composition is set to 100% by mass, the content of the component (F) is preferably 0.5% by mass or more, more preferably 1% by mass or more, and more preferably 1.5% by mass or more. The upper limit is preferably 5% by mass or less, more preferably 4% by mass or less, and more preferably 3% by mass or less.
[0170] From the viewpoint of significantly obtaining the desired effect of the present invention, when the resin component in the resin composition is set to 100% by mass, the content of the component (F) is preferably 1% by mass or more, more preferably 3% by mass or more, and further preferably 5% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less.
[0171] <(G) Organic filler>
[0172] The resin composition may further contain an organic filler as a component (G) as an optional component. The organic filler as the component (G) does not include substances that meet the above-mentioned components (A) to (F). The component (G) may be used alone or in combination of two or more.
[0173] (G) component exists in the resin composition in a granular form. As (G) component, for example, rubber particles, polyamide microparticles, silicone particles, core-shell particles, etc. can be listed. In the present invention, from the viewpoint of significantly obtaining the desired effect of the present invention, it is preferred to use any one of rubber particles and core-shell particles, and it is more preferred to use rubber particles.
[0174] As the rubber component contained in the rubber particles, for example, polybutadiene, polyisoprene, polychloroprene, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-isobutylene copolymer, acrylonitrile-butadiene copolymer, isoprene-isobutylene copolymer, isobutylene-butadiene copolymer, ethylene-propylene-diene terpolymer, ethylene-propylene-butylene terpolymer and other olefin-based thermoplastic elastomers; thermoplastic elastomers such as acrylic thermoplastic elastomers such as poly(meth) propyl acrylate, poly(meth) butyl acrylate, poly(meth) cyclohexyl acrylate, poly(meth) octyl acrylate, etc., preferably olefin-based thermoplastic elastomers, more preferably styrene-butadiene copolymer. Furthermore, the rubber component can be mixed with silicone rubber such as polyorganosiloxane rubber. The glass transition temperature of the rubber component contained in the rubber particles is, for example, 0°C or less, preferably -10°C or less, more preferably -20°C or less, and further preferably -30°C or less.
[0175] As the rubber particles, commercially available products may be used, and examples thereof include "EXL2655" manufactured by Dai Chemika Japan Co., Ltd. and "AC3401N" and "AC3816N" manufactured by Ika Industries Co., Ltd.
[0176] The core-shell type particles are granular organic fillers composed of core particles containing the rubber components listed above and one or more shells covering the core particles. Furthermore, the core-shell type particles are preferably core-shell graft copolymer particles composed of core particles containing the rubber components listed above and a shell obtained by graft copolymerization of monomer components copolymerizable with the rubber components contained in the core particles. The core-shell type mentioned here does not necessarily refer only to materials in which the core particles and the shells can be clearly distinguished, but also includes materials in which the boundary between the core particles and the shells is not obvious, and the core particles may not be completely covered by the shells.
[0177] The rubber component preferably contains 40% by mass or more, more preferably 50% by mass or more, and further preferably 60% by mass or more in the core-shell graft copolymer particles. The upper limit of the content of the rubber component in the core-shell graft copolymer particles is not particularly limited, but is preferably 95% by mass or less, 90% by mass, from the viewpoint of fully covering the core particles with the shell portion.
[0178] Examples of the monomer component forming the shell portion of the core-shell graft copolymer particles include (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, and glycidyl (meth)acrylate; (meth)acrylic acid; N-substituted maleimides such as N-methylmaleimide and N-phenylmaleimide; maleimide; α,β-unsaturated carboxylic acids such as maleic acid and itaconic acid; aromatic vinyl compounds such as styrene, 4-vinyltoluene, and α-methylstyrene; (meth)acrylonitrile, etc., preferably (meth)acrylates, more preferably methyl (meth)acrylate.
[0179] Commercially available core-shell type graft copolymer particles include, for example, "CHT" manufactured by Takura Technology Co., Ltd. "; "B602" made by Tukuno UMG; "B602" made by Tukuru Japan Co., Ltd. ”, “パラロイドEXL2603”, “パラロイドEXL2655”, “パラロイドEXL231 1", "パラロイドEXL2313", "パラロイドEXL2315", "パラロイドKM330" , "パラロイドKM336P", "パラロイドKCZ201", "メタブレンC" manufactured by Mitsubishi Rayon Corporation -223A", "Microelectronics E-901", "Microelectronics S-2001", "Microelectronics W-450" A""メタブレンSRK-200", "カネエースM-511" made by カネカ Company, "カネエースM-" 600", "カネエースM-400", "カネエースM-580", "カネエースMR-01", etc. One type of these may be used alone, or two or more types may be used in combination.
[0180] The average particle size (average primary particle size) of the core-shell graft copolymer particles is not particularly limited, but is preferably 20 nm or more, more preferably 50 nm or more, further preferably 80 nm or more, and particularly preferably 100 nm or more, and is preferably 5,000 nm or less, more preferably 2,000 nm or less, further preferably 1,000 nm or less, and particularly preferably 500 nm or less. The average particle size (average primary particle size) of the core-shell graft copolymer particles can be measured using a zeta potential particle size distribution measuring device or the like.
[0181] From the viewpoint of significantly obtaining the effects of the present invention, when the non-volatile component in the resin composition is set to 100 mass%, the content of the component (G) is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and further preferably 0.3 mass% or more, and is preferably 3 mass% or less, more preferably 1.5 mass% or less, and further preferably 1 mass% or less.
[0182] From the viewpoint of significantly obtaining the effects of the present invention, when the resin component in the resin composition is set to 100% by mass, the content of the component (G) is preferably 1% by mass or more, more preferably 2% by mass or more, and further preferably 3% by mass or more, and is preferably 10% by mass or less, more preferably 8% by mass or less, and further preferably 5% by mass or less.
[0183] <(H) Curing Accelerator>
[0184] The resin composition may further contain a curing accelerator as a component (H) as an optional component. The curing accelerator as the component (H) does not include substances that meet the above-mentioned components (A) to (G). By containing the component (H), the curing of the component (A) can be further promoted. The component (H) may be used alone or in combination of two or more.
[0185] As the component (H), for example, phosphorus curing accelerators, urea curing accelerators, guanidine curing accelerators, imidazole curing accelerators, metal curing accelerators, amine curing accelerators, etc. Among them, a curing accelerator selected from amine curing accelerators and metal curing accelerators is preferred, and an amine curing accelerator is particularly preferred.
[0186] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitic acid salt, tetrabutylphosphonium hydrogenated hexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, and tetraphenylphosphonium; Aromatic phosphonium salts such as phosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone addition reactants such as triphenylphosphine-p-benzoquinone addition reactants; tributylphosphine, aliphatic phosphines such as tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine and tricyclohexylphosphine; dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tri(4-ethylphenyl)phosphine, tri(4-propylphenyl)phosphine, tri(4-isopropylphenyl)phosphine, tri(4-butylphenyl)phosphine, tri(4-tert-butylphenyl)phosphine, tri(2,4-dimethylphenyl)phosphine, tri(2,5-dimethylphenyl)phosphine, Aromatic phosphines such as tri(2,6-dimethylphenyl)phosphine, tri(3,5-dimethylphenyl)phosphine, tri(2,4,6-trimethylphenyl)phosphine, tri(2,6-dimethyl-4-ethoxyphenyl)phosphine, tri(2-methoxyphenyl)phosphine, tri(4-methoxyphenyl)phosphine, tri(4-ethoxyphenyl)phosphine, tri(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether, etc.
[0187] Examples of the urea curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, 3-(3,4-dimethylphenyl)-1, Aromatic dimethyl urea such as 1-dimethyl urea, 3-(4-isopropylphenyl)-1,1-dimethyl urea, 3-(4-methoxyphenyl)-1,1-dimethyl urea, 3-(4-nitrophenyl)-1,1-dimethyl urea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethyl urea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethyl urea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethyl urea, N,N-(1,4-phenylene)bis(N',N'-dimethyl urea), N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethyl urea) [toluenebisdimethyl urea], and the like.
[0188] Examples of the guanidine-based curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine.
[0189] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2′-methylimidazolyl-(1′)] imidazole compounds such as 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins.
[0190] As the imidazole-based curing accelerator, a commercially available product may be used, and examples thereof include "1B2PZ", "2MZA-PW", "2PHZ-PW", and "C11Z-A" manufactured by Shikoku Chemical Industries, Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0191] As metal curing accelerators, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. Specific examples of organic metal complexes include organic cobalt complexes such as cobalt acetylacetonate (II) and cobalt acetylacetonate (III); organic copper complexes such as copper acetylacetonate (II); organic zinc complexes such as zinc acetylacetonate (II); organic iron complexes such as iron acetylacetonate (III); organic nickel complexes such as nickel acetylacetonate (II); organic manganese complexes such as manganese acetylacetonate (II). As organic metal salts, for example, zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, etc. can be cited.
[0192] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine; 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene.
[0193] As the amine-based curing accelerator, a commercially available item may be used, and examples thereof include "MY-25" manufactured by Ajinomoto Ficinno Co., Ltd. and the like.
[0194] From the viewpoint of significantly obtaining the effects of the present invention, when the non-volatile component in the resin composition is set to 100% by mass, the content of the component (H) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 0.1% by mass or more, and is preferably 1.5% by mass or less, more preferably 1% by mass or less, and further preferably 0.8% by mass or less.
[0195] From the viewpoint of significantly obtaining the effects of the present invention, when the resin component in the resin composition is set to 100% by mass, the content of the component (H) is preferably 0.5% by mass or more, more preferably 1% by mass or more, and further preferably 1.5% by mass or more, and is preferably 5% by mass or less, more preferably 4% by mass or less, and further preferably 3% by mass or less.
[0196] <(I) Other Additives>
[0197] In addition to the above-mentioned components, the resin composition may also contain other additives as optional components. Examples of (I) other additives include thermoplastic resins; elastomers; polymerization initiators; organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet light absorbers such as benzotriazole-based ultraviolet light absorbers; adhesion improvers such as urea silane; adhesion imparting agents such as triazole-based adhesion imparting agents, tetrazole-based adhesion imparting agents, and triazine-based adhesion imparting agents; antioxidants such as hindered phenol-based antioxidants agent; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (such as phosphate compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen-based flame retardants (such as melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (such as antimony trioxide); dispersants such as phosphate-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers; photopolymerization initiation aids such as tertiary amines; photosensitizers such as pyrazones, anthracenes, coumarins, xanthones, and thioxanthones. (I) Other additives may be used alone or in combination of two or more.
[0198] <(J) Solvent>
[0199] In addition to the above-mentioned non-volatile components, the resin composition may further contain an optional solvent as a volatile component. As the (J) solvent, a known solvent may be appropriately used, and its type is not particularly limited, and an organic solvent is preferred. As the (J) solvent, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, and anisole; alcohol solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, methoxy Ether ester solvents such as methyl propionate; ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene, etc. (J) The solvent may be used alone or in combination of two or more in any ratio.
[0200] In the resin composition, from the viewpoint of significantly obtaining the effect of the present invention, it is preferred to contain 0.5% by mass or more and 3% by mass or less of the (J) solvent relative to 100% by mass of all the components of the resin composition. Specifically, relative to 100% by mass of all the components of the resin composition, the (J) solvent preferably contains 3% by mass or less, more preferably 2% by mass or less, and further preferably 1.5% by mass or less, and preferably contains 0.5% by mass or more, more preferably 0.8% by mass or more, and further preferably 1% by mass or more.
[0201] The method for preparing the resin composition of the present invention is not particularly limited, and examples thereof include a method in which a solvent or the like is added as necessary, and the compounded components are mixed and dispersed using a rotary stirrer or the like.
[0202] <Physical Properties and Applications of Resin Composition>
[0203] The resin composition comprises the components (A), (B) and (C) in combination, so that a cured product having low dielectric properties, high adhesion between conductor layers, and the ability to suppress cracking after decontamination treatment can be obtained. In addition, the resin composition exhibits the characteristic of low melt viscosity. In addition, a cured product having a high glass transition temperature can also be obtained.
[0204] The cured product obtained by thermally curing the resin composition at 190° C. for 90 minutes shows the characteristic of low dielectric loss tangent. Therefore, the aforementioned cured product will realize an insulating layer with low dielectric loss tangent. The dielectric loss tangent is preferably less than 0.005, more preferably less than 0.004, and further preferably less than 0.003. The lower limit of the dielectric loss tangent can be set to 0.0001 or more. The determination of the dielectric loss tangent can be determined according to the method described in the embodiments described later.
[0205] The cured product obtained by heat curing the resin composition at 190° C. for 90 minutes shows the characteristic of low relative dielectric constant. Therefore, the cured product will realize an insulating layer with low relative dielectric constant. The relative dielectric constant is preferably 4.0 or less, more preferably 3.8 or less, and further preferably 3.6 or less. The lower limit of the relative dielectric constant can be set to 2.0 or more. The relative dielectric constant can be measured according to the method described in the examples described below.
[0206] The resin composition is heat cured at 130°C for 30 minutes, and then the cured product obtained by heat curing at 170°C for 30 minutes shows the characteristics of high peel strength between the plated conductor layers. Therefore, the aforementioned cured product will realize an insulating layer with excellent peel strength between the plated conductor layers. The peel strength is preferably 0.1kgf / cm or more, more preferably 0.2kgf / cm or more, and further preferably 0.3kgf / cm or more. The upper limit of the peel strength can be set to 10kgf / cm or less. The determination of the peel strength can be determined according to the method described in the embodiments described later.
[0207] The cured product obtained by heat curing the resin composition at 130°C for 30 minutes and then heat curing it at 175°C for 40 minutes shows excellent crack resistance after decontamination treatment. Therefore, the aforementioned cured product will realize an insulating layer with excellent crack resistance. Specifically, a layer formed by the cured product of the resin composition is formed on both sides of a core material obtained by forming a circular copper pad with a diameter of 350μm into a grid shape at intervals of 400μm in such a manner that the residual copper rate becomes 60%. The layer formed by the aforementioned cured product is roughened. Observe 100 copper pads after roughening treatment, and preferably there are less than 10 cracks. Crack resistance can be measured by the method described in the embodiments described later.
[0208] The resin composition comprises (A) component, (B) component and (C) component in combination, therefore, usually shows the characteristic of low melt viscosity (minimum melt viscosity). Thus, when a resin composition layer is formed on a substrate having wiring on the surface, the wiring on the substrate surface can be well embedded in the resin composition layer. The melt viscosity of the resin composition is preferably less than 2000 poise, more preferably less than 1900 poise, further preferably less than 1800 poise, particularly preferably less than 1700 poise. The lower limit can be, for example, set to more than 1000 poise, etc. The determination of melt viscosity can be determined according to the method described in the embodiments described later.
[0209] The resin composition comprises (A) component, (B) component and (C) component in combination, and therefore, generally exhibits the property of high glass transition temperature (Tg). Therefore, the aforementioned cured product will realize an insulating layer with a high glass transition temperature. The glass transition temperature is preferably above 130°C, more preferably above 140°C, and further preferably above 150°C. The upper limit is not particularly limited, and can be set to 500°C or less. The determination of the glass transition temperature can be determined by the method described in the embodiments described below.
[0210] The resin composition of the present invention can obtain a cured product having low dielectric properties, high adhesion between conductor layers, and capable of suppressing cracking after decontamination treatment. And then, the resin composition of the present invention shows a low melt viscosity, and a cured product having a high glass transition temperature can also be obtained usually. Therefore, the resin composition of the present invention can be suitably used as a resin composition for insulating purposes. Specifically, it can be suitably used as a resin composition for forming an insulating layer (resin composition for forming an insulating layer for forming a conductor layer), and the insulating layer is used to form a conductor layer (including a rewiring layer) formed on the insulating layer.
[0211] In addition, in the multilayer printed wiring board described later, it can be suitably used as a resin composition for forming an insulating layer of a multilayer printed wiring board (resin composition for forming an insulating layer of a multilayer printed wiring board) and a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for forming an interlayer insulating layer of a printed wiring board).
[0212] In addition, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition of the present invention can also be suitably used as a resin composition for forming a rewiring layer (resin composition for forming a rewiring layer) for forming an insulating layer of a rewiring layer, and a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When manufacturing a semiconductor chip package, a rewiring layer can be further formed on the sealing layer.
[0213] (1) A step of laminating a temporary fixing film on a substrate;
[0214] (2) A process of temporarily fixing the semiconductor chip on a temporary fixing film;
[0215] (3) a step of forming a sealing layer on a semiconductor chip;
[0216] (4) a step of peeling the substrate and the temporary fixing film from the semiconductor chip;
[0217] (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip after the substrate and the temporary fixing film are peeled off; and
[0218] (6) A step of forming a rewiring layer as a conductor layer on the rewiring formation layer.
[0219] [Resin sheet]
[0220] The resin sheet of the present invention comprises a support and a resin composition layer provided on the support and formed of the resin composition of the present invention.
[0221] From the viewpoint of thinning the printed wiring board and providing a cured product with excellent insulation even if the cured product of the resin composition is a thin film, the thickness of the resin composition layer is preferably 100 μm or less, more preferably 80 μm or less, and further preferably 50 μm or less. The lower limit of the thickness of the resin composition layer is not particularly limited, and can usually be set to 5 μm or more.
[0222] Examples of the support include films made of plastic materials, metal foils, and release papers, and films made of plastic materials and metal foils are preferred.
[0223] When a film formed of a plastic material is used as a support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate (hereinafter sometimes referred to as "PEN"); acrylics such as polycarbonate (hereinafter sometimes referred to as "PC") and polymethyl methacrylate (PMMA); cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0224] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. The copper foil may be a foil made of a single metal such as copper or an alloy of copper and other metals (such as tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).
[0225] The surface of the support to be in contact with the resin composition layer may be subjected to roughening treatment, corona treatment, or antistatic treatment.
[0226] In addition, as the support, a support with a release layer having a release layer on the surface bonded to the resin composition layer can be used. As the release agent used in the release layer of the support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, urethane resins and silicone resins can be listed. The support with a release layer can use commercial products, for example, PET films having a release layer with an alkyd resin-based release agent as the main component, i.e., "SK-1", "AL-5", and "AL-7" manufactured by Lintech; "Lumira T60" manufactured by Toray Co., Ltd.; "Purex" manufactured by Teijin Co., Ltd.; "Unipil" manufactured by Unichika Co., Ltd., etc.
[0227] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the thickness of the entire support with a release layer is preferably in the above range.
[0228] In one embodiment, the resin sheet may further include other layers as needed. As the other layers, for example, a protective film based on a support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface on the opposite side of the support) can be cited. The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress the adhesion and scratches of dirt on the surface of the resin composition layer.
[0229] The resin sheet can be produced, for example, by preparing a resin varnish obtained by dissolving a resin composition in a solvent, applying the resin varnish on a support using a die coater or the like, and drying the varnish to form a resin composition layer. The solvent is as described above.
[0230] Drying can be carried out by known methods such as heating and blowing hot air. The drying conditions are not particularly limited, and the resin composition layer is dried in such a manner that the solvent content is 10% by mass or less, preferably 5% by mass or less. It also varies depending on the boiling point of the solvent in the resin varnish. For example, when a resin varnish containing 30% to 60% by mass of a solvent is used, the resin composition layer can be formed by drying it at 50°C to 150°C for 3 minutes to 10 minutes.
[0231] The resin sheet can be stored in a roll shape. If the resin sheet has a protective film, it can be used by peeling off the protective film.
[0232] [Printed wiring board]
[0233] The printed wiring board of the present invention includes an insulating layer formed of a cured product of the resin composition of the present invention.
[0234] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet and by a method including the following steps (I) and (II).
[0235] (I) laminating the inner substrate so that the resin composition layer of the resin sheet is bonded to the inner substrate;
[0236] (II) A step of thermally curing the resin composition layer to form an insulating layer.
[0237] The "inner substrate" used in step (I) refers to a member that becomes a substrate of a printed wiring board, and examples thereof include glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, thermosetting polyphenylene ether substrates, and the like. In addition, the substrate may have a conductor layer on one or both sides thereof, and the conductor layer may be patterned. An inner substrate having a conductor layer (wiring) formed on one or both sides of a substrate is sometimes referred to as an "inner wiring substrate". In addition, when manufacturing a printed wiring board, an intermediate product in which an insulating layer and / or a conductor layer should be further formed is also included in the "inner substrate" mentioned in the present invention. In the case where the printed wiring board is a wiring board with built-in components, an inner substrate with built-in components can be used.
[0238] The lamination of the inner substrate and the resin sheet can be performed by, for example, heating and pressing the resin sheet to the inner substrate from the support body side. As a component for heating and pressing the resin sheet to the inner substrate (hereinafter also referred to as a "heating and pressing component"), for example, a heated metal plate (SUS mirror plate, etc.) or a metal roller (SUS roller) can be listed. It should be noted that it is preferred that the heating and pressing component is not directly pressed on the resin sheet, but is pressed through an elastic material such as heat-resistant rubber, so that the resin sheet fully follows the surface unevenness of the inner substrate.
[0239] The lamination of the inner substrate and the resin sheet can be implemented by vacuum lamination. In the vacuum lamination method, the heating and pressing temperature is preferably 60°C to 160°C, more preferably 80°C to 140°C, the heating and pressing pressure is preferably 0.098MPa to 1.77MPa, more preferably 0.29MPa to 1.47MPa, and the heating and pressing time is preferably 20 seconds to 400 seconds, more preferably 30 seconds to 300 seconds. Lamination is preferably implemented under reduced pressure conditions of 26.7hPa or less.
[0240] Lamination can be performed using a commercially available vacuum laminator. Examples of the commercially available vacuum laminator include a vacuum pressure laminator manufactured by Meiki Manufacturing Co., Ltd., a vacuum applicator manufactured by Nicol Materials Co., Ltd., and an intermittent vacuum pressure laminator.
[0241] After lamination, the laminated resin sheet can be smoothed by pressurizing the heating and pressing member at normal pressure (atmospheric pressure), for example, from the support side. The pressurizing conditions for the smoothing treatment can be set to the same conditions as the above-mentioned heating and pressing conditions for lamination. The smoothing treatment can be performed using a commercially available laminator. It should be noted that the lamination and smoothing treatment can be performed continuously using the above-mentioned commercially available vacuum laminator.
[0242] The support may be removed between step (I) and step (II), or may be removed after step (II).
[0243] In step (II), the resin composition layer is thermally cured to form an insulating layer. The thermal curing conditions of the resin composition layer are not particularly limited, and conditions generally used when forming an insulating layer of a printed wiring board can be used.
[0244] For example, the thermal curing conditions of the resin composition layer also vary depending on the type of the resin composition, and the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.
[0245] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature of 50° C. to less than 120° C. (preferably 60° C. to 115° C., more preferably 70° C. to 110° C.) for 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes).
[0246] When manufacturing a printed wiring board, the step of (III) opening holes in the insulating layer, the step of (IV) roughening the insulating layer, and the step of (V) forming a conductor layer can be further implemented. These steps (III) to (V) can be implemented according to various methods known to those skilled in the art for manufacturing printed wiring boards. It should be noted that when the support body is removed after step (II), the removal of the support body can be implemented between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, the formation of the insulating layer and the conductor layer of steps (II) to (V) can be repeatedly implemented as needed to form a multilayer wiring board.
[0247] Step (III) is a step of drilling holes in the insulating layer, thereby forming holes such as through holes and via holes in the insulating layer. Step (III) can be performed using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The size and shape of the hole can be appropriately determined according to the design of the printed wiring board.
[0248] Step (IV) is a step of roughening the insulating layer. Usually, in this step (IV), contamination is also removed. The steps and conditions of the roughening treatment are not particularly limited, and the known steps and conditions commonly used when forming the insulating layer of the printed wiring board can be adopted. For example, a swelling treatment based on a swelling liquid, a roughening treatment based on an oxidant, and a neutralization treatment based on a neutralizing liquid can be sequentially implemented to roughen the insulating layer. The swelling liquid used in the roughening treatment is not particularly limited, and alkali solutions, surfactant solutions, etc. can be listed, preferably alkali solutions, and as the alkali solution, sodium hydroxide solutions and potassium hydroxide solutions are more preferably used. Examples of commercially available swelling solutions include "Suwering Device Securigan P", "Suwering Device Securigan SBU", and "Suwering Device Securigan P" manufactured by Attech Japan. The swelling treatment based on the swelling solution is not particularly limited, and can be performed, for example, by immersing the insulating layer in a swelling solution at 30° C. to 90° C. for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred that the insulating layer be immersed in a swelling solution at 40° C. to 80° C. for 5 to 15 minutes. As the oxidant used in the roughening treatment, there is no particular limitation, and examples thereof include alkaline permanganate solutions in which potassium permanganate and sodium permanganate are dissolved in an aqueous solution of sodium hydroxide. The roughening treatment based on oxidants such as alkaline permanganate solutions is preferably carried out by immersing the insulating layer in an oxidant solution heated to 60°C to 100°C for 10 minutes to 30 minutes. In addition, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. As commercially available oxidants, examples thereof include alkaline permanganate solutions such as "Concentrator Compactor CP" and "Docking Sound Solution Cecurigan P" manufactured by Attech Japan. In addition, as the neutralizing solution used in the roughening treatment, an acidic aqueous solution is preferred, and commercially available products include, for example, "Ridaktion Solyuretion Cecurigant P" manufactured by Attech Japan. The treatment with the neutralizing solution can be performed by immersing the treated surface roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 1 minute to 30 minutes. From the viewpoint of workability, etc., a method in which the object roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 minutes to 20 minutes is preferred.
[0249] In one embodiment, the arithmetic mean roughness (Ra) of the surface of the insulating layer after the roughening treatment is preferably 300 nm or less, more preferably 250 nm or less, and further preferably 200 nm or less. There is no particular limitation on the lower limit, but it is preferably 30 nm or more, more preferably 40 nm or more, and further preferably 50 nm or more. The arithmetic mean roughness (Ra) of the surface of the insulating layer can be measured using a non-contact surface roughness meter.
[0250] Step (V) is a step of forming a conductor layer, and a conductor layer is formed on the insulating layer. The conductor material used in the conductor layer is not particularly limited. In a suitable embodiment, the conductor layer comprises one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer can be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above group (for example, a nickel-chromium alloy, a copper-nickel alloy and a copper-titanium alloy) can be listed. Among them, from the viewpoints of versatility, cost, ease of patterning, etc., of the formation of the conductor layer, preferably a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy, more preferably a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, and further preferably a single metal layer of copper.
[0251] The conductor layer may be a single-layer structure, or a multilayer structure in which two or more single metal layers or alloy layers formed of different types of metals or alloys are stacked. In the case where the conductor layer is a multilayer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.
[0252] The thickness of the conductor layer is based on the design of a desired printed wiring board, and is usually 3 μm to 35 μm, preferably 5 μm to 30 μm.
[0253] In one embodiment, the conductor layer can be formed by plating. For example, the surface of the insulating layer can be plated by a known technique such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. From the perspective of manufacturing simplicity, it is preferably formed by a semi-additive method. An example of forming a conductor layer by a semi-additive method is shown below.
[0254] First, a plating seed layer is formed on the surface of the insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, the useless plating seed layer is removed by etching or the like, so that a conductor layer having a desired wiring pattern can be formed.
[0255] [Semiconductor devices]
[0256] The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be produced using the printed wiring board of the present invention.
[0257] Examples of the semiconductor device include various semiconductor devices used in electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, automobiles, trains, ships, and airplanes).
[0258] The semiconductor device of the present invention can be manufactured by mounting a component (semiconductor chip) on a conductive portion of a printed wiring board. "Conductive portion" refers to "a portion in a printed wiring board where an electrical signal is transmitted", and the portion may be a surface or a buried portion. In addition, the semiconductor chip is not particularly limited as long as it is an electrical wiring element made of a semiconductor.
[0259] The semiconductor chip mounting method when manufacturing a semiconductor device is not particularly limited as long as the semiconductor chip functions effectively. Specifically, there are wire bonding mounting methods, flip chip mounting methods, mounting methods based on stacked layers without solder joints (BBUL), mounting methods based on anisotropic conductive films (ACF), and mounting methods based on non-conductive films (NCF). Here, "mounting method based on stacked layers without solder joints (BBUL)" means: "a mounting method in which a semiconductor chip is directly embedded in a recess of a printed wiring board to connect the semiconductor chip to the wiring on the printed wiring board."
[0260] Example
[0261] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to these examples. It should be noted that in the following description, "parts" and "%" refer to "parts by mass" and "mass %" respectively, unless otherwise specified.
[0262] <Synthesis Example 1: Synthesis of Compound Ca>
[0263] 48.9 g (0.4 mol) of 2,6-dimethylphenol, 272.0 g (1.4 mol) of α,α'-dihydroxy-1,3-diisopropylbenzene, 220 g of xylene and 70 g of activated clay were added to a 1L flask equipped with a thermometer, a condenser, a Dean-Stark water trap and a stirrer, and heated to 120°C while stirring. Furthermore, the temperature was raised to 210°C while removing distilled water using a Dean-Stark tube, and the mixture was reacted for 3 hours. Thereafter, the mixture was cooled to 140°C, 146.69 g (1.2 mol) of 2,6-dimethylphenol was added, and the temperature was raised to 220°C, and the mixture was reacted for 3 hours. After the reaction, the mixture was cooled to 100°C in air, diluted with 300 g of toluene, the activated clay was removed by filtration, and low molecular weight substances such as the solvent and unreacted products were distilled off under reduced pressure, thereby obtaining 365.3 g of an intermediate phenol compound (a). The hydroxyl equivalent (phenol equivalent) of the obtained intermediate phenol compound (a) was 299.
[0264] Into a 2L flask equipped with a thermometer, a condenser and a stirrer, 365.3 g of the intermediate phenol compound (a) and 700 g of toluene were added and stirred at about 85°C. Next, 29.9 g (0.24 mol) of dimethylaminopyridine was added, and 277.5 g (1.8 mol) of methacrylic anhydride was added dropwise over 1 hour when it was considered that all the solids were dissolved. After the addition was completed, the reaction was further reacted at 85°C for 3 hours. The reaction solution was added dropwise to 4000 g of methanol in a 5L beaker that was vigorously stirred with a magnetic stirrer over 1 hour. The obtained precipitate was filtered under reduced pressure using a membrane filter and then dried to obtain a compound Ca having an indane skeleton and a weight-average molecular weight of 1500 of the following structural formula. The structure of compound Ca is shown below. In the formula, m represents an integer of 1 to 100.
[0265] [Chemistry 10]
[0266]
[0267] <Synthesis Example 2: Synthesis of Compound Cb>
[0268] 48.9 g (0.4 mol) of 2,6-dimethylphenol, 272.0 g (1.4 mol) of α,α'-dihydroxy-1,3-diisopropylbenzene, 280 g of xylene and 70 g of activated clay were added to a 1L flask equipped with a thermometer, a condenser, a Dean-Stark water trap and a stirrer, and heated to 120°C while stirring. Furthermore, the temperature was raised to 210°C while removing distilled water using a Dean-Stark tube, and the mixture was reacted for 3 hours. Thereafter, the mixture was cooled to 140°C, 146.6 g (1.2 mol) of 2,6-dimethylphenol was added, the temperature was raised to 220°C, and the mixture was reacted for 3 hours. After the reaction, the mixture was cooled to 100°C in air, diluted with 300 g of toluene, the activated clay was removed by filtration, and low molecular weight substances such as the solvent and unreacted products were distilled off under reduced pressure, thereby obtaining 365.3 g of an intermediate phenol compound. The hydroxyl equivalent (phenol equivalent) of the obtained intermediate phenol compound is 299. 365.3 g of the obtained intermediate phenol compound, 0.184 g (0.001 mol) of 2,4-dinitrophenol (2,4-DNP), 23.5 g (0.073 mol) of tetrabutylammonium bromide (TBAB), 209 g (1.37 mol) of chloromethylstyrene and 400 g of methyl ethyl ketone were added to a 2L flask equipped with a thermometer, a condenser and a stirrer, and the temperature was raised to 75°C while stirring. Next, 48%-NaOHaq was added dropwise to the reaction vessel maintained at 75°C over 20 minutes. After the addition was completed, stirring was continued at 75°C for 4 hours. After 4 hours, the mixture was cooled to room temperature, 100 g of toluene was added, and then 10% HCl was added for neutralization. Thereafter, separation occurred by liquid separation of the aqueous phase, and then liquid separation and washing were performed 3 times with 300 ml of water. The obtained organic phase was concentrated by distillation, and methanol was added to reprecipitate the product. The precipitate was filtered and dried to obtain a compound Cb having the following structural formula and a weight average molecular weight of 1500.
[0269] [Chemistry 11]
[0270]
[0271] <Synthesis Example 3: Synthesis of Active Ester Compound A>
[0272] 320 g (2.0 mol) of 2,7-dihydroxynaphthalene, 184 g (1.7 mol) of benzyl alcohol, and 5.0 g of p-toluenesulfonic acid monohydrate were added to a flask equipped with a thermometer, a dropping funnel, a condenser, a fractionating tube, and a stirrer, and stirred while blowing nitrogen at room temperature. Thereafter, the temperature was raised to 150°C, and the generated water was distilled out of the system while stirring for 4 hours. After the reaction was completed, 900 g of methyl isobutyl ketone and 5.4 g of a 20% aqueous sodium hydroxide solution were added for neutralization, and the water layer was removed by liquid separation, and washed with 280 g of water for 3 times. The methyl isobutyl ketone was removed under reduced pressure to obtain 460 g of a benzyl-modified naphthalene compound (A-1). The obtained benzyl-modified naphthalene compound (A-1) was a black solid with a hydroxyl equivalent of 180 g / equivalent.
[0273] Into a flask equipped with a thermometer, a dropping funnel, a condenser, a fractionating tube, and a stirrer, 203.0 g of isophthaloyl chloride (the number of moles of acyl chloride groups: 2.0 moles) and 1400 g of toluene were added, and the system was replaced with nitrogen under reduced pressure to dissolve. Next, 113.9 g (0.67 moles) of o-phenylphenol and 240 g (the number of moles of phenolic hydroxyl groups: 1.33 moles) of benzyl-modified naphthalene compound (A-1) were added, and the system was replaced with nitrogen under reduced pressure to dissolve. Thereafter, 0.70 g of tetrabutylammonium bromide was dissolved, and the system was controlled to below 60°C while nitrogen purging was performed, and 400 g of a 20% aqueous sodium hydroxide solution was added dropwise over 3 hours. Then, stirring was continued for 1.0 hour under the same conditions. After the reaction was completed, the liquid was allowed to stand for separation, and the water layer was removed. Furthermore, water was added to the toluene layer in which the reactants were dissolved, and the mixture was stirred and mixed for 15 minutes, and the liquid was allowed to stand for separation to remove the water layer. This operation was repeated until the pH of the aqueous layer reached 7. Thereafter, water was removed by decanting to obtain an active ester compound (B-2) having a nonvolatile content of 65% by mass and in a toluene solution state. The active ester equivalent of the obtained active ester compound A was 238 g / eq.
[0274] <Synthesis Example 4: Synthesis of Vinyl Resin B>
[0275] According to Example 1 of International Publication No. 2017 / 115813, 3.0 mol (390.6 g) of divinylbenzene, 1.8 mol (229.4 g) of ethylvinylbenzene, 10.2 mol (1066.3 g) of styrene, and 15.0 mol (1532.0 g) of n-propyl acetate were put into a 5.0 L reactor, and 600 mmol of diethyl ether complex of boron trifluoride was added at 70 ° C to react for 4 hours. After the polymerization solution was stopped by sodium bicarbonate aqueous solution, the oil layer was washed 3 times with pure water, and the polymer was recovered by decompression and devolatilization at 60 ° C. The obtained substance was weighed to confirm that 896.7 g of vinyl resin B was obtained. The weight average molecular weight (Mw) of vinyl resin B is 41300.
[0276] <Manufacture of resin varnish>
[0277] Each component was weighed according to the mass parts described in the table, and 10 parts of MEK and 10 parts of cyclohexanone were further mixed and uniformly dispersed using a high-speed rotary stirrer to obtain a resin varnish.
[0278]
[0279]
[0280] * In the table, the contents of the components (A), (B), (C) and (E) are expressed based on 100% by mass of the resin components in the resin composition. The content of the component (D) is expressed based on 100% by mass of the nonvolatile components in the resin composition.
[0281] In addition, the details of each component described in the table are as follows.
[0282] (A)Ingredients
[0283] · ZX1059: "ZX1059" manufactured by Nippon Steel Chemical & Material Co., Ltd. (mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, functional group equivalent weight 170 g / eq.)
[0284] HP-4032-SS: "HP4032SS" manufactured by DIC Corporation (naphthalene-type epoxy resin, functional group equivalent weight 144 g / eq.)
[0285] NC-3000L: "NC3000L" manufactured by Nippon Kayaku Co., Ltd. (biphenyl type epoxy resin, functional group equivalent weight 272 g / eq.)
[0286] (B) Ingredients
[0287] HPC-8150-62T: "HPC-8150-62T" manufactured by DIC Corporation (functional group equivalent: 223 g / eq., toluene solution: nonvolatile content: 61.5% by mass)
[0288] HPC-8000-65T: "HPC-8000-65T" manufactured by DIC Corporation (functional group equivalent: 229 g / eq., toluene solution with a nonvolatile content of 65% by mass)
[0289] Compound A: Active ester compound A synthesized in Synthesis Example 3
[0290] (C) Ingredients
[0291] Ca: Compound Ca synthesized in Synthesis Example 1
[0292] Cb: Compound Cb synthesized in Synthesis Example 2
[0293] (D) Ingredients
[0294] SO-C2: Spherical silica surface-treated with an amine alkoxysilane compound ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.5 μm, specific surface area 5.8 m 2 / g, Made by Atomtec Co., Ltd.
[0295] (E) Ingredients
[0296] Maleimide compound A: a compound represented by the following formula (1) synthesized by the method described in Synthesis Example 1 of the Invention Association Publication No. 2020-500211 (Mw / Mn=1.81, t″=1.47 (mainly 1, 2 or 3)), a MEK solution having a nonvolatile content of 62% by mass
[0297] [Chemistry 12]
[0298]
[0299] MIR-3000-70MT: "MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd. (a toluene / MEK solution containing 70% by mass of nonvolatile components)
[0300] SLK-6985: "SLK-6985" manufactured by Shin-Etsu Chemical Co., Ltd.
[0301] SLK-1500: "SLK-1500" manufactured by Shin-Etsu Chemical Co., Ltd.
[0302] · OPE-2St-1200: "OPE-2St-1200" manufactured by Mitsubishi Gas Chemical Co., Ltd. (a toluene solution containing 65% by mass of nonvolatile components)
[0303] Vinyl resin B: Vinyl resin B synthesized in Synthesis Example 4
[0304] NE-V-1100-70T: "NE-V-1100-70T" manufactured by DIC Corporation (a toluene solution containing 70% by mass of nonvolatile components)
[0305] (F)Ingredients
[0306] LA-3018-50P: "LA-3018-50P" manufactured by DIC Corporation (1-methoxy-2-propanol solution having a functional group equivalent of 151 g / eq. and a nonvolatile content of 50% by mass)
[0307] (G) Ingredients
[0308] ·EXL-2655:ダウ・ケミカル Made in Japan
[0309] (H) Ingredients
[0310] 1B2PZ: Made by Shikoku Chemical Industry Co., Ltd.
[0311] <Determination of dielectric constant (relative dielectric constant) and dielectric loss tangent>
[0312] (1) Preparation of Resin Sheet A Having a Resin Composition Layer Thickness of 40 μm As a support, a polyethylene terephthalate film ("AL5" manufactured by Lintech, thickness of 38 μm) having a release layer was prepared. The resin varnish obtained in the examples and comparative examples was uniformly applied on the release layer of the support so that the thickness of the resin composition layer after drying was 40 μm. Thereafter, the resin composition was dried at 80°C to 100°C (90°C on average) for 2 minutes to obtain a resin sheet A including a support and a resin composition layer.
[0313] (2) Preparation of Cured Material for Evaluation
[0314] The resin sheet A was cured in an oven at 190° C. for 90 minutes. The support was peeled off from the resin sheet A taken out of the oven to obtain a cured product of the resin composition layer. The cured product was cut into pieces of 80 mm in length and 2 mm in width to prepare a cured product for evaluation.
[0315] (3) Determination of dielectric constant and dielectric loss tangent
[0316] For each evaluation cured product, the dielectric constant / dielectric loss tangent (Dk value / Df value) was measured using a cavity resonance perturbation method using "HP8362B" manufactured by Agilent Technologies, under the conditions of a measurement frequency of 5.8 GHz and a measurement temperature of 23° C. and 90° C. The measurement was performed using two test pieces, and the average value was calculated.
[0317] <Measurement of Peel Strength of Plated Conductor Layer>
[0318] (1) Preparation of Resin Sheet A Having a Resin Composition Layer Thickness of 40 μm As a support, a polyethylene terephthalate film ("AL5" manufactured by Lintech, thickness of 38 μm) having a release layer was prepared. The resin varnish obtained in the examples and comparative examples was uniformly applied on the release layer of the support so that the thickness of the resin composition layer after drying was 40 μm. Thereafter, the resin composition was dried at 80°C to 100°C (average 90°C) for 4 minutes to obtain a resin sheet A including a support and a resin composition layer.
[0319] (2) Preparation of inner substrate
[0320] A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness of 18 μm, substrate thickness of 0.4 mm, "R1515A" manufactured by Panasonic Corporation) with inner layer wiring was etched 1 μm on both sides using a microetchant ("CZ8101" manufactured by Meck Co., Ltd.) to roughen the copper surface.
[0321] (3) Lamination of resin sheet A
[0322] The resin sheet A was laminated on both sides of the inner substrate using an intermittent vacuum pressurizing laminator (manufactured by NICO MATERIALS CO., LTD., two-stage stack laminator "CVP700") so that the resin composition layer was in contact with the inner substrate. The lamination was performed by reducing the pressure for 30 seconds to adjust the air pressure to 13 hPa or less, and then pressing them for 30 seconds at 120°C and a pressure of 0.74 MPa. Then, heat pressing was performed for 60 seconds at 100°C and a pressure of 0.5 MPa.
[0323] (4) Thermal curing of resin composition layer
[0324] Thereafter, the inner substrate laminated with the resin sheet A was placed in an oven at 130°C and heated for 30 minutes, and then transferred to an oven at 170°C and heated for 30 minutes to thermally cure the resin composition layer to form an insulating layer. Thereafter, the support was peeled off to obtain a cured substrate A having an insulating layer, an inner substrate, and an insulating layer in this order.
[0325] (5) Roughening treatment
[0326] A desmearing treatment as a roughening treatment was performed on the cured substrate A. As the desmearing treatment, the following wet desmearing treatment was performed.
[0327] The cured substrate A was immersed in a swelling liquid ("Suiling Dip Securigant P" manufactured by Attech Japan, an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 5 minutes, and then immersed in an oxidizing agent solution ("Concentrator Compact CP" manufactured by Attech Japan, an aqueous solution with a potassium permanganate concentration of about 6% and a sodium hydroxide concentration of about 4%) at 80°C for 20 minutes. Next, in the neutralizing solution ("Rytronic System" manufactured by Atotron Co., Ltd. After being immersed in "Coronolant P", sulfuric acid aqueous solution) at 40°C for 5 minutes, it was dried at 80°C for 15 minutes.
[0328] (6) Formation of Conductor Layer
[0329] The conductor layer is formed on the roughened surface of the insulating layer according to the semi-additive method. 2 After being immersed in an electroless plating solution at 40°C for 5 minutes, the substrate was immersed in an electroless copper plating solution at 25°C for 20 minutes. Then, after being heated at 150°C for 30 minutes for annealing, a resist layer was formed, and patterning was performed by etching. Thereafter, copper sulfate electrolytic plating was performed to form a conductor layer with a thickness of 25 μm, and annealing was performed at 190°C for 60 minutes. The obtained substrate is referred to as "evaluation substrate A".
[0330] (7) Determination of peel strength of plated conductor layer
[0331] The peel strength between the insulating layer and the conductor layer was measured in accordance with Japanese Industrial Standard (JIS C6481). Specifically, a scratch of 10 mm in width and 100 mm in length was made on the conductor layer of the evaluation substrate A, one end of the scratch was peeled off and clamped with a clamp, and the load (kgf / cm) when peeling 35 mm in the vertical direction at a speed of 50 mm / min at room temperature was measured to obtain the peel strength. In the measurement, a tensile tester ("AC-50C-SL" manufactured by TSE Corporation) was used.
[0332] <Evaluation of Crack Resistance after Decontamination Treatment>
[0333] As a support, a polyethylene terephthalate film ("AL5" manufactured by Lintech, with a thickness of 38 μm) having a release layer was prepared. The resin varnish obtained in the examples and comparative examples was uniformly applied on the release layer of the support so that the thickness of the resin composition layer after drying was 25 μm, and dried at 70° C. to 80° C. (75° C. on average) for 2.5 minutes to obtain a resin sheet B comprising a support and a resin composition layer.
[0334] Using an intermittent vacuum pressurized laminator (a two-stage stacking laminator "CVP700" manufactured by Niccolo Materiel), a core material ("E705GR" manufactured by Lezonak, with a thickness of 400 μm) was formed into a grid shape with a circular copper pad (copper thickness of 35 μm) of 350 μm at intervals of 400 μm in a manner that the residual copper rate was 60%. The resin sheet B was laminated on both sides of the inner substrate in such a manner that the resin composition layer was bonded to the inner substrate. The lamination was performed by reducing the pressure for 30 seconds and setting the air pressure to 13 hPa or less, and then pressing for 30 seconds at a temperature of 100°C and a pressure of 0.74 MPa. It was placed in an oven at 130°C and heated for 30 minutes, then transferred to an oven at 175°C and heated for 40 minutes. Furthermore, the support body was peeled off, and the obtained wiring board was immersed in the swelling liquid, Semenstron P manufactured by Atotron Co., Ltd., at 60° C. for 10 minutes. Next, as a roughening liquid, Kontech P (KMnO) manufactured by Atechnik Co., Ltd. 4 The copper pads of 100 roughened wiring substrates were observed, and the presence or absence of cracks in the resin composition layer was evaluated according to the following criteria.
[0335] ○: The number of cracks is 10 or less.
[0336] △: The number of cracks is more than 10 and 20 or less.
[0337] ×: There are more than 20 cracks.
[0338] <Measurement of Melt Viscosity>
[0339] The resin sheet A was peeled from the support film and measured using a dynamic viscoelasticity measuring apparatus G-3000 manufactured by Yubiem Co., Ltd. at a frequency of 1 Hz, a strain of 5 degrees, a load of 100 g, a heating rate of 5°C / min, and a temperature range of 60°C to 180°C.
[0340] <Measurement of glass transition temperature (Tg)>
[0341] The resin sheet A was cured in an oven at 190°C for 90 minutes, and then the support was peeled off to obtain a cured film. The cured film was cut into a length of 20 mm and a width of 6 mm to obtain a cured sample for measuring the linear thermal expansion coefficient. For the cured sample, a TMA device (thermomechanical analysis device, manufactured by Rigaku Co., Ltd.) was used to measure Tg. The details are as follows: After the cured sample was installed in the aforementioned device, two measurements were performed continuously under the measurement conditions of a load of 1g and a heating rate of 5°C / minute (the first measurement was heated from 25°C to 220°C, and the second measurement was heated from 25°C to 250°C), and the second value was recorded.
[0342]
[0343]
Claims
1. A resin composition comprising: (A) Epoxy resin; (B) an active ester compound; and (C) a compound represented by formula (C-1), [Chemistry 1] In formula (C-1), X each independently represents an n-valent hydrocarbon group optionally having a substituent; Y each independently represents a monovalent group optionally having a substituent and containing a double bond; Ar each independently represents a divalent aromatic hydrocarbon group having two alkyl groups that are optionally the same or different as substituents; Z each independently represents a single bond or a divalent aromatic hydrocarbon group optionally having a substituent; n represents an integer of 1 to 3; and m represents an integer of 1 to 100.
2. The resin composition according to claim 1, wherein Y represents any one of an acryloyl group, a methacryloyl group, and a vinylbenzyl group.
3. The resin composition according to claim 1, wherein The component (C) contains a compound represented by formula (C-2), [Chemistry 2] In formula (C-2), R 1 and R 2 Each independently represents a monovalent group containing a double bond; R 3 and R 4 Each independently represents a divalent aromatic hydrocarbon group having two alkyl groups which may be the same or different as substituents; R 5 Each independently represents a divalent aromatic hydrocarbon group; R 6 represents a single bond or a divalent aromatic hydrocarbon group which may have a substituent; and m1 represents an integer of 1 to 100.
4. The resin composition according to claim 1, wherein The component (C) contains a compound represented by formula (C-3), [Chemistry 3] In formula (C-3), R 11 and R 12 Each independently represents a monovalent group containing a double bond; R 13 and R 14 Each independently represents a divalent aromatic hydrocarbon group having two alkyl groups which may be the same or different as substituents; R 15 represents a single bond or a divalent aromatic hydrocarbon group which may have a substituent; and m2 represents an integer of 1 to 100.
5. The resin composition according to claim 1, wherein When the resin component in the resin composition is 100 mass %, content of the component (C) is 1 mass % or more and 25 mass % or less. The resin composition according to claim 1 , further comprising (D) an inorganic filler. 7 . The resin composition according to claim 1 , further comprising (E) a compound having a double bond.
8. The resin composition according to claim 7, wherein When the resin component in the resin composition is 100 mass %, content of the component (E) is 1 mass % or more and 25 mass % or less. 9 . The resin composition according to claim 1 , further comprising (F) a curing agent. 10 . A resin sheet comprising a support and a resin composition layer, wherein the resin composition layer is provided on the support and comprises the resin composition according to claim 1 . 11 . A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to claim 1 .
12. A semiconductor device comprising the printed wiring board according to claim 11.
Citation Information
Patent Citations
Soluble polyfunctional vinyl aromatic copolymer, method for producing same and curable composition
WO2017115813A1
Curable resin composition and cured product
WO2023008079A1